Antidepressant, Antidiarrheal, Thrombolytic and Phytochemical Profiling of Ethanol Extract of Amomum aromaticum Leaves: In vivo and In vitro Approaches (Bangladesh Pharmaceutical Journal, 2024)
The study evaluated several pharmacological effects including antidepressant, antidiarrheal and thrombolytic activities of ethanol extract of Amomum aromaticum leaves (EEAA). Upon the assessment for qualitative phytochemical groups in the extract, several doses of EEAA (1000 - 4000 mg/kg) were studied to find acute oral toxicity in mouse for safe dose selection. Then EEAA was tested whether it demonstrates antidepressant activity in tail suspension test (TST) and forced swim test (FST). Antidiarrheal and clot lysis activities of EEAA were evaluated in castor oil-induced diarrhoea in mouse and In vitro clot lysis method, respectively. Oral administration of EEAA (1000 - 4000 mg/kg) showed no morality after 10 days, and no sign of acute toxicity observed within 24 hrs post-treatment. The qualitative phytochemical screening showed the presence of carbohydrate, alkaloid, flavonoid, tannin, saponin, and polyphenol groups in EEAA. The TST and FST resulted with significant improvement in mobility in mice treated with EEAA (400 mg/kg), where fluoxetine (20 mg/kg) was used as standard in both tests. EEAA treatment also showed a moderate dose-dependent anti-diarrheal effect. The 400 mg/kg oral dosing for 14 days decreased the rate of defecation by 52.8% compared to the control group. This study also demonstrated that EEAA possesses clot lysis activity. Hence, further intense investigations are suggested to identify specific potential active phytochemicals.Bangladesh Pharmaceutical Journal 27(1): 51-58, 2024 (January)